Potential of Lacto-Gypsum as an Amendment to Build Soil Quality - Bondi, Giulia; Fenton, Owen; Sawdekar, Parikshit; Keane, Hilda; Wall, David P. (Frontiers in Sustainability, 2021)
Strategies for the use of amendments on agricultural soils are needed to help build resilience against potential soil threats. Gypsum is commonly applied to improve soil quality and nutrient supply. However, the sustainability and environmental safety of some gypsum sources is uncertain. This study aims to i. characterize a new by-product, lacto-gypsum, derived from a dairy whey side stream over a 1 year pilot production cycle and ii. assess the temporal variability of the raw form of lacto-gypsum and the stability of its physico-chemical and compositional properties when stored under three potential storage regimes. Results showed that lacto-gypsum compares favorably with conventional equivalents in terms of nutrient and trace element concentrations and represents an environmentally safe material free of contaminants. Storage form did not affect its main physico-chemical characteristics over time and the raw lacto-gypsum remained stable up to 20 days when stored at 4°C. In contrast to conventional gypsum, the lacto-gypsum had very low pH. In general this new lacto-gypsum shows potential as a suitable product for use as a soil amendment or as an acidification agent for animal slurry to reduce ammonia gas emissions during storage. However, further evaluation of this by-product in real life scenarios is required.